(untitled) (Health and Biosciences, 2021)
The changes that occurred in the last decades in the population’s lifestyle, stimulated by the capitalist market of large food companies and influenced by the agglomeration of population in large urban centers associated to an exhaustive workload of the workers, promoted a rise in the consumption of food from outside the home and consequently the increase in the number of commercial establishments in this sector, especially in the fast-food segment. However, the technical capacity of the professionals linked to the aforementioned establishments regarding hygiene did not follow the expansion, since there was a concomitant increase in the percentage of foodborne diseases in the country. As the information about the hygiene conditions of fast-food enterprises is still incipient and fragmented, this work had the objective of analyzing the hygienic-sanitary conditions of fast food restaurants in Brazil from a narrative review of literature. We have evaluated studies published since 1980, prospected in several databases. In a holistic way, the analysis of the results of the studies ratifies that the hygienic conditions of the fast food services are unsatisfactory and points to the necessity of carrying out continuous training in good practices of food handling.